Study the analysis of porous medium on performance of heat transfer flow - Sekkizhar, A.; Selvaraj, A. (International Journal of Engineering and Technology, 2018)
In this paper think about the strength investigation of two dimensional normal flat constrained convective warmth exchange through permeable medium with info and yield is existed. A uniform temperature is applied in one side of the wall and other side of wall is separately. The brinkman and Darcy model used for flow in the porous medium. Parametric equations are analyzed and determine the effects heat transfer through porous channel. Reynolds number, Nusselt number and contact factor are set up for a model of permeable warmth exchange dependent on the present a specific technique.Â Â